Câncer de cabeça e pescoço : significados para profissionais de enfermagem - Reis, Juliana Benevenuto (2013)
This study had as the main objective to understand the meanings involving the care of people with head and neck cancer (HNC) under the nursing professionals’ perspective. The head and neck oncology is the specialty that treats malignant neoplasies located on the lips, oral cavity, oropharynx, nasopharynx, larynx, salivary glands, thyroid, and parathyroid, among others (PARISE; KOWALSKI; LEHN, 2008). The implications of this cancer are related to the involvement of regions and organs responsible for respiration, digestion, and phonation. Surgeries involving this region are generally ablative and can affect the face so impactful for the patient, family, and health professionals. Due to the altered body image, readjustments must be made by the ill person, his family, and even the professionals who care for them in relation to emotional support and all the implications that the disease can cause. This research was carried out by descriptive and qualitative approach through a field study using interviews with twelve nurses who provide care for people with HNC in a reference unit in the State of Mato Grosso, Brazil. Based on nursing professionals' narratives, four categories were established that show the overview of how the professional interprets the care of patients with HNC. The categories were: “The interpretation of the patient with HNC by nursing professionals; The HNC repercussions on the treated patient; The communication; and Guidelines for practice”. Issues such illness, death, pain and suffering, family, and disfigurement were highlighted in the discussions. It is concluded that these discussed issues will subsidize reflections about how the nurse sees the person with HNC; and with this how they can understand and stimulate discussions on these themes in everyday health practice.